Peningkatan Keterampilan Kolaborasi dan Keterlaksanaan Pembelajaran IPA Secara Daring Melalui Lesson Study - Salasiah Salasiah; Dwi Hariyanto; Tri Ahini; Anita Widhiastuti; Rabiatul Adawiyah; Erdiningsih Erdiningsih; Moh Anang Hermansyah; Agus Haryono* (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
The COVID-19 pandemic in Indonesia and around the world is still on going. Teaching and learning activities in schools require a change, one of which is by using the internet network (online) to maintain the implementation and quality of learning outcomes. Lesson Study can improve student collaboration skills, teacher collaboration and implementation of learning. The implementation of lesson study (LS) at SMPN 1 Palangka Raya in collaboration with Palangkaraya University has been carried out in 2 cycles. The implementation of LS in Natural Science (IPA) material is carried out by 4 model teachers and 7-8 observers. Each cycle consists of stages: Lesson Design, Redesign, Open Class, and Reflection. The implementation of learning and collaboration of teachers or students is measured using an observation sheet. Observational data were analyzed descriptively and qualitatively. The results showed that collaboration skills between teachers were obtained in the first cycle of 85.94%, an increase in the second cycle of 96.88%. The activity of teachers in one LS Team reached 100%, while during the Open Class in the first cycle it was 80.08% and the second cycle was 76.83%. The implementation of learning for 8 open lessons from 4 teachers for the first cycle was 93.75% and the second cycle was 95.83%. Students' collaboration skills increased from cycle I (77.08%) to Cycle II (91.67%). Thus, the application of LS to online science materials at SMPN 1 Palangka Raya City can be applied to increase collaboration during the covid-19 pandemic